Turkish Administrators' Views of School-Family Cooperation Through the Pandemic - AYDOS, EMİNE HANDE; Türk, Endam Düzyol; YAĞAN, SEVCAN (Routledge Journals, Taylor & Francis Ltd., 2025)
We aimed to understand the views of preschool administrators on the changing process of school-family cooperation studies with COVID-19 pandemic and distance education process. We used phenomenological approach as a qualitative method. The participants identified through snowball sampling consisted of five administrators from five kindergartens. To reveal the experiences of administrators, data was collected through a semi-structured interview form that included questions related to pre-pandemic, the beginning, middle, and end of the pandemic period. The findings of the research have been presented under specific themes. Before the pandemic, family involvement activities and parent meetings were organized for specific days and weeks; however, with the pandemic, administrators who did not know what to do in the first place used online platforms to stay in touch with parents and children. In the middle of the pandemic, their collaborative efforts diversified and both administrators and teachers in different schools have stated that they collaborated with each other on how to conduct parent involvement. Administrators added a positive change in parents' perspectives on early childhood education during the pandemic, with increased awareness, influence and emphasized the importance of active parental involvement in education processes.
Keywords: Administrator; Crisis; Distance Education; Preschool; School-family Cooperation